Halogen-induced internal heavy-atom effect shortening the emissive lifetime and improving the fluorescence efficiency of thermally activated delayed fluorescence emitters. Issue 46 (21st November 2017) - Xiang, Yepeng; Zhao, Yongbiao; Xu, Nan; Gong, Shaolong; Ni, Fan; Wu, Kailong; Luo, Jiajia; Xie, Guohua; Lu, Zheng-Hong; Yang, Chuluo
Abstract : A halogenating electron acceptor is demonstrated as a feasible strategy for shortening emissive lifetimes while improving the fluorescence efficiency of TADF emitters. Abstract : Halogenation of an electron acceptor in TADF emitters is presented as a feasible strategy for shortening the DF lifetimes of TADF emitters without sacrificing their photoluminescence quantum yields. A greenish-yellow device based on the chloride-substituted emitter (ClPPM ) achieves a high external quantum efficiency of 22.2% and an ultra-slow efficiency roll-off of 12.3% at a practical luminance of 1000 cd m −2, which is comparable to the state-of-the-art device performance for green-to-yellow TADF OLEDs at the practical luminance.